2017
DOI: 10.22159/ijpps.2017v9i11.21827
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Artocarpus Lakoocha Extract and Oxyresveratrol Against Hydrogen Peroxide-Induced Toxicity in Sh-Sy5y Cells

Abstract: Objective: Artocarpuslakoocha Roxb. Is a traditional medical plant native to Southeast Asia and used as a dried aqueous extract so-called puaghaad. Its role (and its major ingredient, oxyresveratrol) as an antioxidant neuroprotectant were explored.Methods: Differentiated SH-SY5Y neuroblastoma cells in 96-well plates were challenged with 200 µM H2O2 for 4h and either Trolox (100 µM), oxyresveratrol (5-100 µM), or puaghaad (1.2-25 µg/ml) applied 2h before H2O2 or for 20 h after H2O2Results: Continuous presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Our previous study revealed that A. lakoocha extract (containing OXY as a major compound) decreased the lipopolysaccharide (LPS)-mediated release of nitric oxide (NO), MCP-1, IL-6, and TNF-α in RAW 264.7 macrophages by suppressing the phosphorylation of PI3K/AKT and the activation of NF-κB signal transduction pathway [10]. Interestingly, OXY has been reported to pass the blood-brain barrier in rats, exhibit neuroprotective effects in SH-SY5Y cells against hydrogen peroxide (H 2 O 2 ) induction, ameliorate NLRP3 inflammasome activation, and block nuclear translocation of NF-κB molecule in rat cortical neuronal cells in response to glucose or oxygen deprivation [12][13][14]. Moreover, OXY presents its neuroprotective ability by counteracting reactive oxygen species (ROS) in activated mouse murine N9 microglia [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that A. lakoocha extract (containing OXY as a major compound) decreased the lipopolysaccharide (LPS)-mediated release of nitric oxide (NO), MCP-1, IL-6, and TNF-α in RAW 264.7 macrophages by suppressing the phosphorylation of PI3K/AKT and the activation of NF-κB signal transduction pathway [10]. Interestingly, OXY has been reported to pass the blood-brain barrier in rats, exhibit neuroprotective effects in SH-SY5Y cells against hydrogen peroxide (H 2 O 2 ) induction, ameliorate NLRP3 inflammasome activation, and block nuclear translocation of NF-κB molecule in rat cortical neuronal cells in response to glucose or oxygen deprivation [12][13][14]. Moreover, OXY presents its neuroprotective ability by counteracting reactive oxygen species (ROS) in activated mouse murine N9 microglia [15].…”
Section: Introductionmentioning
confidence: 99%